Orally added black maca (Lepidium Meyenii Walp.) Nano-emulsion meliorates fresh semen quality, testosterone level and fertilising ability of chilled and cryopreserved rabbit buck spermatozoa - Khlood G. Abdelkhalek; Amal M. Aboelmaaty; Fady S. Youssef; Mohamed F. Mohamed; Abdelraouf M. Ghallab; Mostafa M. Abou-Ahmed (World Rabbit Science)
Maca is an economic crop grown in the highlands of South America that serves as a food source and medication for humans and animals. The goal of this study was to determine the potential beneficial effects of administering the nano-emulsion of black maca (Lepidium meyenii) orally to improve fresh, chilled and frozen rabbit semen, as well as its promising effects on fertilising ability and testosterone levels. The study included forty New Zealand mature white rabbit bucks (8 to 10 mo old) and eighty non-lactating, sexually receptive New Zealand white rabbit does. Rabbit bucks were divided into a control group and treatment groups. The control group was given 0.0 mg maca (M0) nano-emulsion. Treatment groups M60, M120 and M180 were orally given 60 mg, 120 mg and 180 mg, respectively, of maca nano-emulsion. Maca was administered orally twice a week for 10 wk. Rabbit does were divided into four equal groups and prepared for insemination with chilled and frozen semen from the best concentration of the treatment (M60=980±69.65×106/mL spermatozoa) and the control. Semen was collected and evaluated once weekly for 10 wk, and testosterone hormone was also analysed once at fortnightly intervals for the same period. Results revealed that maca significantly increased (P<0.05) ejaculate volume (0.41 vs. 0.56 mL for M0 vs. M60), sperm progressive motility (61.00 vs. 75.19% for M0 vs. M60), sperm count, the total number of sperm per ejaculate and testosterone levels (0.45 vs. 1.5 ng/mL for M0 vs. M60). It also improved sperm morphology compared to the control. M60 was the most effective concentration, so semen was collected from M60 rabbit bucks, chilled and frozen and used in the fertilising ability test. Finally, administering the nano-emulsion of black maca orally (60 mg/twice weekly/buck/10 wk) has been suggested for increasing rabbit buck semen quality, testosterone hormone levels and fertilising ability of chilled and cryopreserved rabbit buck spermatozoa. The pregnancy and kindling rates were 66.66 vs. 100% for M0 vs. M60 of chilled semen, as well as 33.33 vs. 83.33% for frozen/thawed sperm.